How do Glial Cells Contribute to Motor Control? - Christensen, Rasmus K.; Petersen, Anders V.; Perrier, Jean-Francois (Current Pharmaceutical Design, 2013)
For many years, glial cells from the central nervous system have been considered as support cells involved in the homeostasis of the brain. However, a series of key-findings obtained during the past two decades has put light on unexpected roles for glia and it is getting more and more admitted that glia play an active role in several physiological functions. The discovery that a bidirectional communication takes place between astrocytes (the star shaped glial cell of the brain) and neurons, was a major breakthrough in the field of synaptic physiology. Astrocytes express receptors that get activated by neurotransmitters during synaptic transmission. In turn they release other transmitters - called gliotransmitters - that bind to neuronal receptors and modulate synaptic transmission. This feedback, which led to the concept of the tripartite synapse, has been reported with various transmitters including glutamate, ATP, GABA or serine. In the present review we will focus on astrocytes and review the evidence suggesting and demonstrating their role in motor control. Rhythmic motor behaviors such as locomotion, swimming or chewing are generated by networks of neurons termed central pattern generators (CPG). These networks are highly flexible and adjust the frequency of their output to the external environment. In the case of respiration, the CPG reacts when changes in the pH of the blood occur. The chemosensory control of breathing is ensured by astrocytes, which react to variation of the blood pH by releasing ATP on neurons that in turn adapt the frequency of respiration. In the spinal cord, diverse transmitters such as ATP, adenosine or endocannabinoids modulate the CPG responsible for locomotion. A growing body of evidence suggests that glial cells release some of these molecules. These data suggest that astrocytes play an essential role in motor control and we believe that a range of studies will confirm this view in the near future.
Keywords: glutamate